Periapical cyst in odontopediatric patient: a case report (Research, Society and Development, 2020)
The purpose of this article is to describe a case report of a mandible chronically inflamed root cyst on a pediatric patient. A 6 year old male patient attended the Pediatric Dentistry Clinic with the chief complain tooth pain and swelling on the right side of the face. On clinical and radiological findings it was observed that the 84 tooth had a grayish coloration, radiolucent image temporary restoration on the furca that extended from the 84 to 85 region. The treatment consisted of the extraction of the deciduous teeth 84 and 85 and cystic lesion for histopathological analysis. The patient returned 7 days after surgery with an tissue healing. Histopathological examination revealed a cystic cavity with a thin, 2-3-layer non-keratinized cubic epithelial lining. Cystic capsule, represented by fibrous connective tissue with hemorrhagic areas and intense inflammatory infiltrate with congested vessels. It was then diagnosed as a chronically inflamed root odontogenic cyst. Enucleation may be considered the most suitable alternative to treat of these lesions, reducing the chances of relapse.